Caffeine Targets G6PDH to Disrupt Redox Homeostasis and Inhibit Renal Cell Carcinoma Proliferation - Xu, Huanhuan; Hu, Lihong; Liu, Titi; Chen, Fei; Li, Jin; Xu, Jing; Jiang, Li; Xiang, Zemin; Wang, Xuanjun; Sheng, Jun (Frontiers in Cell and Developmental Biology, 2020)
Glucose-6-phosphate dehydrogenase (G6PDH) is the rate-limiting enzyme in the pentose phosphate pathway (PPP) and plays a crucial role in the maintenance of redox homeostasis by producing nicotinamide adenine dinucleotide phosphate (NADPH), the major intracellular reductant. G6PDH has been shown to be a biomarker and potential therapeutic target for renal cell carcinoma (RCC). Here, we report a previously unknown biochemical mechanism through which caffeine, a well-known natural small molecule, regulates G6PDH activity to disrupt cellular redox homeostasis and suppress RCC development and progression. We found that caffeine can inhibit G6PDH enzymatic activity. Mechanistically, caffeine directly binds to G6PDH with high affinity (KD = 0.1923 μM) and competes with the coenzyme NADP+ for G6PDH binding, as demonstrated by the decreased binding affinities of G6PDH for its coenzyme and substrate. Molecular docking studies revealed that caffeine binds to G6PDH at the structural NADP+ binding site, and chemical cross-linking analysis demonstrated that caffeine inhibits the formation of dimeric G6PDH. G6PDH inhibition abrogated the inhibitory effects of caffeine on RCC cell growth. Moreover, inhibition of G6PDH activity by caffeine led to a reduction in the intracellular levels of NADPH and reactive oxygen species (ROS), and altered the expression of redox-related proteins in RCC cells. Accordingly, caffeine could inhibit tumor growth through inhibition of G6PDH activity in vivo. Taken together, these results demonstrated that caffeine can target G6PDH to disrupt redox homeostasis and inhibit RCC tumor growth, and has potential as a therapeutic agent for the treatment of RCC.